Load shedding in power system using new optimization method lighting search algorithm - Khayatry Tamil Selvam (2023)
In developing countries like Malaysia, sustainable or reliable supply of electrical energy plays vital role in fulfilling the demand of end users. The vast majority rely on upon electrical vitality in every aspect of their life. All divisions in Malaysia highly depend on sable and consistent power supply without and disturbances. For instance, large manufacturing industries will face seroius financial implication if there ara any disturbance that will cause downtime even for a day.